On Bosnian Sanjakbey Skender-Pasha and His Descendants - Zlatar, Behija (Prilozi za orijentalnu filologiju, 2017)
On the basis of the Ottoman and Western sources, the paper presents a biography of the famous Bosnian sanjakbey, Rumeli beylerbey and vezier Skender-pasha, who is at the same time one of the most important persons in the history of Bosnia from the end of the 15th and the beginning of the 16th centuries, and it is enriched by new data which is correcting some of the statements from the earlier historiography. It is not known precisely where was Skender-pasha born, but it is known that his father was from Genoa and his mother was a Greek. He was extremely able and successful general and he was involved in numerous military operations of the Ottoman army. He held a position of Bosnian sanjakbey for three times, from 1478 to 1480, 1485 to 1490, and from 1499 until his death in 1506. In the meantime he was a Rumeli beylerbey and vezier. As a Bosnian sanjakbey he maintained good relations with Ragusans, who often used to send him gifts, and he helped them in trading business in return, or mediated in their disagreements with their neighbors. He left a visible trace in the urban development of cities, and especially Sarajevo, where he established endowments in the left side of river Miljacka, place still called by his name – Skenderija, as well as on Kovači and Vratnik. Apart from that, he established pious endowments in Istanbul, and he also founded Nova Varoš. This paper also gives information on Skender-pasha’s descendants who also held important positions in Rumeli eyalet.